Reseña de Varile. G. B. y A. Zampolli (eds) (1997): Survey of the State of the Art in Human Language Technology. Linguistica Computazionale. vol. XII-XIII. Giardini Editori e Stampatori in Pisa., Pisa, Italy. - Zarco Tejada, M. Ángeles (Pragmalingüística, 2021)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña de Varile. G. B. y A. Zampolli (eds) (1997): Survey of the State of the Art in Human Language Technology. Linguistica Computazionale. vol. XII-XIII. Giardini Editori e Stampatori in Pisa., Pisa, Italy.